Abnormalities in Brain and Muscle Microstructure and Neurochemistry of the DMD Rat Measured by in vivo Diffusion Tensor Imaging and High Resolution Localized 1H MRS - Xu, Su; Tang, Shiyu; Li, Xin; Iyer, Shama R.; Lovering, Richard M. (Frontiers in Neuroscience, 2020)
Duchenne muscular dystrophy (DMD) is an X-linked disorder caused by the lack of dystrophin with progressive degeneration of skeletal muscles. Most studies regarding DMD understandably focus on muscle, but dystrophin is also expressed in the central nervous system, potentially resulting in cognitive and behavioral changes. Animal models are being used for developing more comprehensive neuromonitoring protocols and clinical image acquisition procedures. The recently developed DMD rat is an animal model that parallels the progressive muscle wasting seen in DMD. Here, we studied the brain and temporalis muscle structure and neurochemistry of wild type (WT) and dystrophic (DMD) rats using magnetic resonance imaging and spectroscopy. Both structural and neurochemistry alterations were observed in the DMD rat brain and the temporalis muscle. There was a decrease in absolute brain volume (WT = 1579 mm3; DMD = 1501 mm3; p = 0.039, Cohen’s d = 1.867), but not normalized (WT = 4.27; DMD = 4.02; p = 0.306) brain volume. Diffusion tensor imaging (DTI) revealed structural alterations in the DMD temporalis muscle, with increased mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD). In the DMD rat thalamus, DTI revealed an increase in fractional anisotropy (FA) and a decrease in RD. Smaller normalized brain volume correlated to severity of muscle dystrophy (r = −0.975). Neurochemical changes in the DMD rat brain included increased GABA and NAA in the prefrontal cortex, and GABA in the hippocampus. Such findings could indicate disturbed motor and sensory signaling, resulting in a dysfunctional GABAergic neurotransmission, and an unstable osmoregulation in the dystrophin-null brain.